Visions of colonial Nairobi: William Simpson, health, segregation and the problems of ordering a plural society, 1907-1921 - Greenwood, Anna; Topiwala, H. (Oxford University Press, 2018)
The 1915 Simpson Report made public health recommendations for Nairobi that were heralded as ground-breaking. Of particular interest to the colonial authorities was Professor Simpson’s suggestion to racially segregate Nairobi to prevent diseases said to emanate from its Indian bazaar. Rather than being novel, this article shows that these recommendations were typical of enthusiasm for segregation in other parts of Empire, as well as being in line with earlier health reform proposals for Nairobi. Furthermore, although public health justified racially discriminatory practices for European ends, this was not a predictable story of Indians uniting against segregation and Europeans campaigning for it. Indeed, the debates stimulated by Simpson reveal some disunity amongst Kenyan Indians. Additionally, when segregation plans were dropped in 1921 Indians continued to live in their own sub-communities in Nairobi, indicating that opposition to segregation was as much a symbolic political battle than a cultural necessity.